Pedagogical competency training for teachers of inclusive school at SDN 2 Petir - Komarudin Komarudin; David Sulistiawan Aditya (Universitas Muhammadiyah Magelang, 2023)
The constitutional mandate that every citizen has the right to an equitable education is reflected in inclusive schools. However, it can be challenging for inclusive schools to offer the best education due to the many features of students, both cognitively normal and those with special needs. This is because of a lack of pedagogical expertise, particularly among teachers who lack a base in inclusive education. Therefore, this community service program aims to provide pedagogical competency training for SDN 2 Petir teachers. Community service activities are carried out in three stages, namely preparation, implementation and evaluation. The training was delivered through seminars on the practice of early identification of ABK and the practice of collecting ABK profiles, as well as information on inclusive schools and the characteristics of ABK. The evaluation's findings demonstrated that the training significantly improved the pedagogical knowledge and abilities of SDN 2 Petir teachers.